AÇÕES EDUCATIVAS INTERDISCIPLINARES COM CRIANÇAS EM IDADE ESCOLAR: ALTERNATIVAS PARA A PREVENÇÃO DA OBESIDADE INFANTIL - LIMA, KARINE APARECIDA DE (2022)
This dissertation aimed to promote interdisciplinary educational actions and to evaluate the effectiveness of this methodology on the acceptability, consumption and knowledge of vegetables among school-age children. A total of 793 children aged 7 to 10 years old, enrolled in the 2nd, 3rd, 4th or 5th year of schools in the city of Guarapuava, PR, participated in the research. In the first stage of the research (Chapter 2), 793 children were organized into 2 groups: control group and intervention group. In the intervention group, 400 children participated in educational activities: setting up a school vegetable garden, recreational activities / training and cooking workshops (watercress kibbeh, Swiss chard roll, honey bread with eggplant flour, spinach pancake and radish pie). In the control group, 393 children tasted and sensory evaluated the same foods prepared in the workshops by the intervention group, however without participating in any educational activity. The products were imposed in relation to sensory analysis and physicochemical composition. All products have high acceptability indexes (>70%), which are well accepted by children. In the second stage of the research (Chapter 3), the 400 children in the intervention group (Chapter 2) were evaluated through questionnaires, pre and post-intervention, in relation to the degree of learning of the themes in the interdisciplinary actions. In addition, they were evaluated in relation to their nutritional status, in which most children were eutrophic, especially as girls, however, a significant number of children were overweight (31,5%). In general, as interdisciplinary interventions related to food and nutrition, when carried out jointly as a school garden, cooking workshop and other theoretical and practical play activities, they are effective in improving the acceptability of products made with vegetables of low acceptance and/or knowledge among school-age children (p<0,05). Therefore, educational actions on food and nutrition education in the school environment are effective in helping to improve eating habits in childhood, encouraging the consumption of foods with a good nutritional profile, which contributes to the prevention of childhood obesity and a reduction in the associated risk of diseases.